Kenya's informal milk markets and the regulation–reality gap. (1st March 2022) - Blackmore, Emma; Guarin, Alejandro; Vorley, William; Alonso, Silvia; Grace, Delia
Summary: Motivation: Around 80% of milk in Kenya is marketed informally, providing livelihoods and contributing to the food security and nutrition of low‐income consumers. Government policy, however, is focused on formalization—primarily through licensing and pasteurization—with enforcement via fines, confiscation of milk, or closing the premises of informal actors. Purpose: This article seeks to better understand if, and why, Kenya's informal milk sector and regulatory system are disconnected from one another and how the policy–reality gap might be better bridged. Methods and approach: To understand the nature and performance of Kenya's informal milk markets and their governance, we used a mix of research methods and data sources, including surveys with informal market players, and key informant interviews with key sector stakeholders. Fieldwork was carried out in Nairobi in late 2018. Findings: Milk safety and quality matters to all actors in informal milk value chains. The trust‐based system used is effective in moderating behaviours and assessing and prioritizing quality and safety. Government policy is not accomplishing the stated goal of formalization: licensing levels remain low among informal actors. Pasteurization is not rewarded in the market. There is some evidence of suboptimal pasteurization processes being undertaken to satisfy regulators. There is a gap between the reality of Kenya's informal milk sector and its regulatory system. Policy implications: The regulation–reality gap manifests itself as adversarial relationships between regulators and informal actors, and unnecessary transaction costs, missing opportunities for enhancing livelihoods, food safety, and food security. New approaches should build on and consider existing approaches taken by actors in informal food markets to ensure food safety and quality. Policy‐makers should seek to communicate more effectively with informal actors and engage in more constructive dialogue on inclusive ways forward.